Penipuan dengan Menggunakan Telepon Seluler Ditinjau dari KUHP - Theodorus Rumampuk (Unisia, 2007)
Nowadays the development of technology in telecommunication becomes more sophisticated. In this connection it has been seen the tool of communication that is cellular phone. The function of this phone can be able to help human to communicate the message to other people in the distant location. But the negative impact of this phone for instance deception by short message service. In this sense, the problem is the deception could be classified as a criminal according to KUHP. According to the writer this kind of deception could be classified criminal act based on article 378-395 of KUHP.